2017
DOI: 10.21162/pakjas/17.4674
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR CHARACTERIZATION OF Fusarium oxysporum F. SP. CUBENSE (FOC) TROPICAL RACE 4 CAUSING PANAMA DISEASE IN CAVENDISH BANANA IN PAKISTAN

Abstract: Fusarium wilt or Panama disease poses a great risk to banana production worldwide and is caused by Fusarium oxysporum f. sp. Cubense (Foc). Its tropical race 4 (TR4) is a major problem for Cavendish banana growing areas. Basrai (Dwarf Cavendish) is the major cultivated variety in Pakistan and now recently been reported to be affected by Foc TR4 in certain areas in the Sindh province. To genetically characterize, three independent isolates (P.TH1, P.TH2 and P.Th3) were sampled from different fields in district … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Fusarium oxysporum f. sp. cubense (Foc; TR4) was acquired from the Tissue culture department of National Agricultural Research Centre (NARC), Islamabad, the identity of which has been molecularly confirmed [ 66 ]. After the revival of Foc culture on potato dextrose agar (PDA), its morphology was examined, showing 3–5 septate, hyaline, sickle-shaped, macroconidia pointed at both ends and borne on single phialides, whereas microconidia were found to be mostly hyaline, kidney-shaped, aseptate produced on false heads.…”
Section: Methodsmentioning
confidence: 99%
“…Fusarium oxysporum f. sp. cubense (Foc; TR4) was acquired from the Tissue culture department of National Agricultural Research Centre (NARC), Islamabad, the identity of which has been molecularly confirmed [ 66 ]. After the revival of Foc culture on potato dextrose agar (PDA), its morphology was examined, showing 3–5 septate, hyaline, sickle-shaped, macroconidia pointed at both ends and borne on single phialides, whereas microconidia were found to be mostly hyaline, kidney-shaped, aseptate produced on false heads.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, race TR4 was found in Jordan, the first official report of the presence of TR4 in the Southeast Asia-Pacific region. In 2014 survey conducted found another infected area in the North of the original outbreak [11,12] reporting that TR4 is a serious problem for the Cavendish group of banana developing zones in Pakistan noting that cv. Basrai to be affected by TR4 in specific areas in the Sindh territory creating devastation for the banana industry and seriously affecting the Pakistani economy.…”
Section: Plate1 Panama Wilt Infected Banana Orchards Atmentioning
confidence: 99%
“…Detection of pathogen is an important consideration and conventionally, pathogenicity test and Vegetative compatibility grouping (VCG) are deployed which having some bottleneck [34,35]. Recently PCR based detection method have been considered as reliable protocol for early and accurate detection of the isolate identity followed by apprehension of diversity and species synteny [23,30,36].…”
Section: Pcr Detection Of the Foctr4 Isolatementioning
confidence: 99%